(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: Formalin is being used for preservation of biological specimens including cadavers in laboratories and dissection halls of medical colleges worldwide. It is used as disinfectant and preservative solution in Anatomy mortuaries, Pathological laboratories, Hospitals and plastic industries. Exposure occurs mainly by inhalation. This study was planned to assess effects of exposure to formalin on lung function of medical students. Method: Spirometry was done before exposure, after acute exposure and at end of academic year. Results were analysed. Results: There was significant decrease in values of FVC, FEV1,FEF25-75, FEF.2-1.2 and MVV (p<0.05) after acute exposure to formalin. There was no any noticeable change in FEV1/FVC ratio(p>0.05). Though the PEFR was decreased after acute exposure it was not up to a statistically significant level (p>0.05). Thevalues of FVC, FEV1, FEF25-75, FEF.2-1.2 and MVV which were reduced significantly after acute exposure came to normal after chronic exposure. The FEV1/FVC ratio was almost same (p>0.05). PEFR was significantly increased (p<0.05) compared to that after acute exposure. Conclusion: In Anatomy dissection hall local exhaust ventilation system should be installed and personal protective equipments such as safety eyeglasses and gloves should be made available and used to reduce exposure to FA and prevent adverse effects on health of students.